Adsorption Behavior of Copper in Some Calcareous Soils from Duhok Governorate - Lazkeen A. M. Mehmedany; Farhad A. Hashim; Vahel I. H. Barwari (Science Journal of University of Zakho, 2016)
Soil samples were taken from the surface layer of eight locations (Smail Ava, Khanki, Khirshanya,  Esyan, Mahed, Suwaratoka, Bamerny and Tirwanish) Duhok governorate -Iraqi Kurdistan region, to evaluate the adsorption and thermodynamic parameters of copper (Kº, ∆Gº, ∆Hº and ∆Sº) which were determined using adsorption data and Cu2+ in equilibrium solution at two different temperature. The results demonstrated that an concentration increasing in adsorbed Cu2+with increasing added Cu2+ and temperature in all studied soils. The values of the thermodynamic equilibrium constant (Kº) and ∆Gº increased with increasing temperature from (25 to 48) °C. The values of ΔGº of both temperatures (25°C and 48°C) were negative, ranged from (-16.505 to -17.346 and -18.658 to -21.519) kJ mol-1 respectively, these negative values designate that the adsorption process is spontaneous. Enthalpy (ΔHº) and entropy (∆Sº) of studied soils were positive and varied from (2.678 to 36.716) kJ mol-1 and (66.466 to 181.417) J mol-1K-1. The positive results of (ΔHº) showed that Cu2+ adsorption is an endothermic reaction. The results also revealed that alkaline calcareous soils in Duhok adsorbed high quantities of Cu2+ and thermodynamic parameters are helpful in describing Cu2+ adsorption. The high value of Kº, ∆Gº, ∆Hº and ∆Sº for copper at 25°C and 48°C were found in soil of Smail Ava location, but low value of ∆Hº and ∆Sº for copper initiate in soil of Suwaratoka location. The type of adsorption process in Khirshanya and Suwaratoka locations can be explained by ion exchange because the mean free energy of adsorption (E) value in both locations were less than 16 kJ mol-1.